Financial Inclusion and Access to Higher Education An Empirical Study of Selected Districts in Eastern Uganda - Eton, Marus; Sammy, Godfrey Poro; Denis, Sekiwu; Fabian, Mwosi; Francis Akena, Adyanga (European Journal of Business and Management, 2020)
Access to higher education has continuously been a challenge in Uganda. The research brought out the relationship between financial inclusion and access to higher education. Descriptive survey research design was adopted and the findings established that digital financing eases making deposits in banks, transacting via mobile money and switching from one bank to the other. Students find it easy to deposit tuition in the bank just as they find it easy to access money via mobile money. While financial inclusion makes financial services available in the economy, students, especially those from low-income families find difficulty accessing a wider range of these products, which hinders their access to higher education. The study also establishes that a good number of students fail to meet admission requirements. Since students from low-income families attend high schools of low quality, they have insufficient understanding of some subjects, and thus unable to join higher education. Online registration and payment, students’ decision not to join, peer influence, and rigidity of university programs; are deeply flawed to limit accessing higher education. However, financial services remain accessible to rich individuals who demonstrate ability to pay. The study recommends that the government of Uganda through the concerned ministry should review the implementation of their policies on Students loan scheme and district quota systems. The government should always publish the lists of students admitted to higher education institutions in popular media and newspapers to create awareness to those being admitted to particular institutions.